I think it’s C. I plugged it on to a graph and shows that graph a is steeper than graph b. red is graph a. blue is graph b.
Answer:
The value of f(x) - g(x) is:
f(x) - g(x) = 2x² + 6x - 4
Step-by-step explanation:
Given
f(x) = 3x² + x - 3
g(x) = x² - 5x + 1
To determine
f(x) - g(x)
Using the formula
f(x) - g(x) = 3x² + x - 3 - ( x² - 5x + 1)
= 3x² + x - 3 - x² + 5x - 1
= 2x² + 6x - 4
Therefore, the value of f(x) - g(x) is:
f(x) - g(x) = 2x² + 6x - 4
y = ( 48 *2 ) / 6
Step-by-step explanation:
If y varies directly as x they are directly proportional, which means they relate to each other in the same way....
2 : y = 6: 48
what is y if x = 2?
The value of y can be found if you write it a two fracrions
2 : y = 6 : 48
2 / y = 6 / 48
cross multiply the fractions gives
6*y = 48 *2
divide left and right of the = sign by 6 gives the answer:
y = ( 48 *2 ) / 6
(if you solve it you get y = 12 but that was not the question).
Other method:
multiply left and right of the = sign by y
2 * y/y = y *6 / 48
6y / 48 = 2 * 1
multiply left and right of the = sign by 48
6y * 48/48 = ( 48 *2 )
6y = ( 48 *2 )
divide left and right of the = sign by 6
6/6* y = ( 48 *2 )/6
y = ( 48 *2 ) / 6
(if you solve it you get y = 12 but that was not the question).
Answer:
Everything
Step-by-step explanation:
We can keep every things in the blank boxes.
Step-by-step explanation:
G(x) = 2/3 x - 6 switch x and y around and solve for y.
y = 2/3 x - 6
x = 2/3 y - 6
x + 6 = 2/3 y
3/2 x + 9 = y